PENGARUH STRUKTUR MODAL, PROFITABILITAS DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DI BIDANG MANUFAKTUR (SUB SEKTOR TEKSTIL) YANG TERDAFTAR DI BEI PERIODE 2019-2024 - Maria Feronica; SIgit Santoso (Jurnal Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of capital structure, profitability, and liquidity on firm value in manufacturing companies within the textile and garment subsector listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. This study employs a quantitative method with a panel data approach combining time series and cross-sectional data. The research sample consists of 8 textile and garment subsector companies selected using a purposive sampling technique. The data used are secondary data obtained from the companies’ annual financial reports and were analyzed using multiple linear regression with the assistance of SPSS software. The results show that capital structure and profitability partially have a positive but insignificant effect on firm value, while liquidity has a positive and significant effect on firm value. Simultaneously, capital structure, profitability, and liquidity do not have a significant effect on firm value.